Optimization of Science Learning Outcomes for Series and Parallel Electrical Circuits Through Project-Based Learning Methods for Grade VI Elementary School - Halimah, Siti; Wibowo, Setiawan Edi; Bafirman, Bafirman (STKIP Singkawang, 2024)
This study aims to improve student learning outcomes in the subject of series and parallel electrical circuits in Class VI of Inpres Seringgu Elementary School in the 2023/2024 academic year by implementing a project-based learning methodology. This method was chosen because it can activate direct student involvement in the learning process, provide practical experience, and encourage the development of critical and collaborative thinking skills. In this study, students were invited to design and build simple projects related to electrical circuits, such as lamps that can be turned on through series and parallel electrical circuits. This research was carried out as a class action consisting of two cycles. Each cycle includes planning, implementation, observation, and reflection. Data were obtained through observation, interviews, and assessment of learning outcomes. The results of data analysis showed a significant increase in student learning outcomes. The average score before the application of the project-based method was 65, which increased to 80 in the first cycle and 90 in the second cycle. In addition, student involvement during learning also increased, as seen from the enthusiasm and active participation in discussions and practical activities. Therefore, the application of the project-based learning methodology has shown its effectiveness in improving student learning outcomes in the concept of electrical circuits. This study advocates the application of analogous strategies in other subjects to enhance conceptual understanding and enhance students' practical abilities. This research makes a constructive contribution to improving pedagogical approaches in primary education, with a particular emphasis on the field of science